“I want to talk about it, but at the same time, I don't want to, so it's just easier to draw it”: perceived benefits of an arts-based intervention to support children's basic psychological needs and well-being - Jasmine Piché; Fahim Moominzada; Zachary Dylan Fry; Sandrine Corbeil; Laurie Deschenes; Emilie Mclean; Kyra Simons; Adrianna Mendrek; Catherine Malboeuf-Hurtubise (Frontiers in Health Services, 2026)
Children from low-income families and rural areas are particularly vulnerable to developing emotional and behavioral problems. Implementing mental health intervention into after-school programs can serve as an opportunity to foster the well-being of these children. Arts-based interventions appear particularly effective at engaging children in reflections on daily challenges and processing associated emotions and thoughts, thus supporting their well-being. Study Aims In collaboration with an after-school program, this study aimed to explore the perceived benefits of an arts-based intervention on children’s well-being and document how the intervention supported their self-determination. Methods An 8-week arts-based intervention was implemented in an after-school program. Using a qualitative design, semi-structured interviews ( n =14) were conducted with the participants and the after-school program coordinators ( n =1) to capture their perspectives of the intervention. Focus groups and observational data were used to enrich the data from the interviews. Inductive-deductive thematic analyses were used to document the emerging themes. Results Two main themes emerged from the interviews with the coordinators. First, the intervention fostered the development of positive and secure relationships, between the research team and the particpants, among participants themselves, and between participants and program coordinators. Second, the intervention provided an opportunity to develop socioemotional competencies and coping skills. Three main themes emerged from the interviews with the participants. The intervention provided a safe and supportive environment where children were able to develop self-awareness and consciousness of others, as well as foster emotional expression and positive affect. Moreover, the intervention supported, to some extent, children’s basic psychological needs for autonomy, competence, and relatedness Implications These findings provide support to the existing literature on arts-based interventions in fostering children mental health. This type of intervention appeared to be particularly beneficial for underprivileged children, as it is non-threatening and less confronting than other mental health interventions.